Aspek Penerapan Wireless Sensor Network Untuk Mendeteksi Pencemaran Udara Akibat Kabut Asap Kebakaran Hutan - Natanael Firnandus M; Indra Yasri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Air pollution effect of the forest fire become one of important issues in Indonesia. Air pollution can be bad for impact community which able to eliminate the visibility when driving and also become worse for person who having respiratory problem. Therefore is needed an accurate and real-time system for monitoring the level of air pollution base on WSN. This work purposes sensor placement survey to achieve efficiency on routing protocol. The survey will focus on directed diffusion and cluster directed diffusion protocol. The reason to select this two routing protocol base on their performance indicator which cover average delay, total energy and lowest life node. All process of design will perform through Java Simulator.Keywords : Sensor Placement, Wireless Sensor Network, Directed Diffusion, Clustering, Average Delay, Efficiency Energy, Lowest Life Node.